Deskripsi Penggunaan Media Cerita Bergambar Pada Pembelajaran di Sekolah Dasar - Hilmi Aziz; Dessy Setyowati; Ady Setiawan (PT. ALHAFI BERKAH INDONESIA, 2024)
Teachers still use the conventional approach (lectures) and lack the use of learning media used in the teaching and learning process. This results in students being less motivated to learn so that there are still many students who are not fluent in reading, some are not paying attention to the teacher when explaining, talking to their classmates, ignoring when the teacher tells them to do assignments. The method used in this research uses a descriptive method with a qualitative approach. This research provides a precise description and explanation of the conditions or symptoms encountered. Data collection technique. The data collection technique used in this research is Document Study. Characteristics of pictorial media: In the first characteristic, the program is equipped with a 2D animation application which can create animated cartoons, interactive animations, games, company profiles, presentations, video clips, movies, web animations and other applications as many as 15 articles out of the 20 articles that have been analyzed, this is shows that the presentation is 75% fulfilled regarding these characteristics. The second characteristic is that the image media program is equipped with interactive buttons with movies or certain objects. 12 articles out of the 20 articles that have been analyzed, show a 60% presentation regarding these characteristics. The third characteristic is that the image media is equipped with a program that can make changes in color transparency, 8 of the 20 articles analyzed showed a percentage of 40% regarding this characteristic. Furthermore, there is a fourth characteristic, namely image media equipped with animation that can follow a predetermined path. The researchers got 11 out of 20 articles which showed a percentage of 55% regarding this characteristic. Furthermore, finally, there are characteristics of flash programs that are equipped with vector-based animation which has flexibility in creating vector objects, 20 of the 20 articles that have been analyzed, this shows that the percentage is 100% fulfilled regarding these characteristics.